Urbanización Cesar Calvo de Araujo - Iquitos - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observo las casas de la Urbanización Cesar Calvo de Araujo.
ENGLISH: The houses of Urbanización Cesar Calvo de Araujo were observed.

SPANISH: Se observo las casas de la Urbanización Cesar Calvo de Araujo.
ENGLISH: The houses of Urbanización Cesar Calvo de Araujo were observed.
Cesar Calvo de Araujo Urbanization - Iquitos
Keywords: Iquitos (Perú)|~|Urbanization|~|Urban structures|~|Houses|~|Perú|~|Urbanization|~|Iquitos (Perú)|~|Urbanización|~|Estructura Urbana|~|Casas|~|Perú|~|Urbanización|~|Iquitos (Peru)|~|Urbanization|~|Urban Structure|~|Houses|~|Peru|~|Urbanization